Reaction of soybean cultivars to Meloidogyne javanica and Meloidogyne incognita - Mazzetti, Valéria Cecília Ghissi; Visintin, Gustavo Luiz; Valério, Igor Pirez; Camera, Juliane Nicolodi; Deuner, Carolina Cardoso; Soares, Pedro Luiz Martins [UNESP] (Universidade Federal de Viçosa, 2019)
Nematodes of the genus Meloidogyne are associated with soybean cultivation, unknown the reaction of cultivars. The objective of this work was to determine the reaction of soybean cultivars to M. javanica and M. incognita. Twenty-seven soybean cultivars were sown in plastic pots, in a completely randomized experimental design with eight replicates. Ten days after emergence of the seedlings, in a separate experiment, M. javanica and M. incognita were inoculated. For M. javanica, cultivars classified as susceptible were BMX Lança IPRO, AMS Tibagi RR, BMX Vanguarda IPRO, NS 6700 IPRO, BMX Ativa RR, FPS Solimões RR, TEC 6702 IPRO, NS 5909 RR, NS 5445 IPRO, 54i52 RSF IPRO, M 6410 IPRO and NS 5959 IPRO and BMX Elite IPRO, NA 6211 RR, BMX Valente RR, FPS Júpter RR, FPS Iguaçú RR, BMX Tornado RR, GMX Cancheiro RR, TMG 7161 IPRO, TMG 7062 IPRO, FPS Solar RR, M 5730 IPRO, DM5958 RSF IPRO, NS 6006 IPRO, SYN 1163 RR and M 5947 IPRO were resistant. Regarding M. incognita, the resistant cultivars were FPS Iguaçú RR, FPS Solar IPRO, SYN 1163 RR and TMG 7062 IPRO. The cutlivars FPS Júpter RR, SYN 1163 RR e TMG 7062 IPRO were resistant to both nematodes.
Keywords: reproduction factor; resistance; root-knot nematode; susceptibility